2016
DOI: 10.1016/j.neuron.2016.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Proneurogenic Ligands Defined by Modeling Developing Cortex Growth Factor Communication Networks

Abstract: The neural stem cell decision to self-renew or differentiate is tightly regulated by its microenvironment. Here, we have asked about this microenvironment, focusing on growth factors in the embryonic cortex at a time when it is largely comprised of neural precursor cells (NPCs) and newborn neurons. We show that cortical NPCs secrete factors that promote their maintenance, while cortical neurons secrete factors that promote differentiation. To define factors important for these activities, we used transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 25 publications
2
66
0
Order By: Relevance
“…However, the predominant cells are the radial precursors and newborn neurons, and we therefore hypothesized that during this developmental window, the cortical growth factor environment is largely determined by these two cell types. In our very recently published work, 4 we provided support for this hypothesis, and in the course of our studies, obtained a global overview of the growth factor environment during cortical neurogenesis. Here, we will discuss those studies and their implications for our understanding of neural precursor cells and neural development.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…However, the predominant cells are the radial precursors and newborn neurons, and we therefore hypothesized that during this developmental window, the cortical growth factor environment is largely determined by these two cell types. In our very recently published work, 4 we provided support for this hypothesis, and in the course of our studies, obtained a global overview of the growth factor environment during cortical neurogenesis. Here, we will discuss those studies and their implications for our understanding of neural precursor cells and neural development.…”
supporting
confidence: 60%
“…During the early neurogenic period in the embryonic cortex, the predominant cell types are the radial precursor cells (RPs), which populate the Ventricular/Subventricular Zones adjacent to the lateral ventricles, and newborn cortical neurons (Neurons) that migrate along the radial precursor basal processes to populate the Cortical Plate. In our recent paper 4 we showed that radial precursors produce secreted factors that act in an autocrine fashion to promote their own self-renewal, while newborn cortical neurons produce secreted factors that act in a paracrine fashion to enhance the genesis of neurons from radial precursors. We modeled these potential cell-cell communication networks, and identified 3 growth factors, GDNF, NRTN and IFNg, that promote neurogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, transcriptomic data may be used to predict partners by their co-expression with CD24 (Ayre et al, 2016), similar to the approach that identified novel ligand-receptor interactions regulating neuronal stem cell renewal (Yuzwa et al, 2016). Alternatively, identifying common signaling outcomes between CD24 and cell specific surface receptors could be used to predict receptor partners.…”
Section: Identifying Cd24 Mechanismsmentioning
confidence: 99%
“…Moreover, this integration provides more information than any one signaling network alone, such as coincidence detection. Importantly, two recent publications utilizing transcriptomic profiling in development support this notion and demonstrate unexpected instances of interaction and integration [169,170]. The task of characterizing the temporal and spatial profiles of a molecular network is itself a difficult undertaking.…”
Section: Consequences Of Spatial and Temporal Molecular Network: mentioning
confidence: 99%